(untitled) (Submission and Review of Research -Biological Sciences Series, 2025)
An experiment was conducted in columns (diameter 25 cm, height 40 cm) in a greenhouse in 2023, filled with clay loamy soil. The study included the following treatments: Control 1, filled with soil and no amendments or basic mineral N, P, K fertilization; Control 2 received mineral fertilization only; treatments received mineral fertilization in addition to amendments either cattle manure (OM), or biochar (B), or both (OM+B). Amendments were added at a rate of 4% of each. The experiment was carried out for 70 days during which columns received weekly irrigation with distilled water using drips. Leachates were collected from column 24 hours after irrigation. Leachate volume, nutrient concentrations were measured and total nutrients leached were calculated, Nitrate is the main form of mineral nitrogen in leachate in the treatment Control 2 which constituting 73% of the total. The addition of cattle manure and biochar reduced leaching of NO3 by 95.5 and 92%, respectively, and this rate increase to 99.5% when both cattle manure and biochar were added together. Both amendments separately or jointly reduced the cumulative NH4+ leached from the soil by 77, 71, and 67%, respectively. Cattle manure increased leaching total dissolved phosphorus TDP by a rate of 45%, while biochar alone or in combination with cattle manure reduced TDP leaching by 58.5 and 19%, respectively.